Technological Peer Pressure and Product Disclosure - Cao, Sean Shun; Ma, Guang; Tucker, Jennifer Wu; Wan, Chi (The Accounting Review, 2018)
ABSTRACT We introduce a firm-specific measure of the technological aspect of competition—technological peer pressure—and examine firm-initiated product development-related press releases. We argue that empirical examinations of the theorized negative relation between competition and disclosure require the type of voluntary disclosure to be relevant to the dimension of competition under examination to ensure that firms incur significant proprietary costs of disclosure. In other words, many types of disclosure do not provide actionable information to competitors and, thus, should not be affected by that dimension of competition. We expect a negative relation between technological peer pressure and product disclosure because the latter reveals firms' strategies, allocations, and progress of technological investments in product development to competitors. In contrast, we do not expect a negative relation between technological peer pressure and management earnings forecasts—the most common type of voluntary disclosure used in accounting research. Our test results are consistent with these expectations. Data Availability: All data are available from public sources. Our TPP Measure is available for download, please see the link in Appendix G.